PENINGKATAN KETERAMPILAN MEMBACA PEMAHAMAN MENGGUNAKAN STRATEGI GUIDE READING DI KELAS VI SD NEGERI 104/II SUNGAI PINANG: KETERAMPILAN MEMBACA PEMAHAMAN, STRATEGI GUIDE READING - Apdoludin Apdoludin; Reni Guswita; Nur Habibah; Ahmad Ridhoh; Putri Nadila Aswa (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
The problem in this study is that students' initial reading skills are still low. This results in low reading ability. This study aims to determine the increase in reading comprehension skills after implementing the Guide Reading strategy in learning Indonesian in Class VI students of SD Negeri 104/II Sungai Pinang. This research is a classroom action research, which was conducted in class VI of SDN 104/II Sungai Pinang with a total of 22 students consisting of 11 girls and 11 boys for the subject of Indonesian Language Education. This research was carried out in Semester II of the 2022-2023 Academic Year which was divided into two cycles. The results showed that there was an increase in reading comprehension skills after implementing the Guide Reading strategy, where the learning process in cycle I met 60% teacher aspects and 58% student aspects and in cycle I meeting II teacher aspects 73% and student aspects 75% while cycle II meetings I teacher aspect 80% and student aspect 70% and cycle II meeting II teacher aspect 85% and student aspect 80%. There was an increase in reading comprehension skills using the Guide Reading strategy from cycle I with a percentage of 75.86% to cycle II with a percentage of 93%. It was concluded that the use of the Guide Reading strategy can improve students' reading comprehension skills.